Bullying: a responsabilidade civil e o dever de indenização - Konig, Evelin Sofia R (2013)
Bullying is a relatively recent phenomenon, but with extremely harmful consequences to social harmony. They refer to moral and or physical assaults supported by the lack of tolerance and respect towards others. Thus, this paper questions the liability of schools facing their students and the civil liability of parents toward their minor children. Rooted on the precept of no harm to others, emerges the obligation to repair damages of any nature